An unusual variation of extensor digitorum brevis manus: A case report and literature review - (:unkn) unknown (CHURCHILL LIVINGSTONE INC MEDICAL PUBLISHERS, 1998)
An unusual variation of the extensor digitorum brevis manus in a male cadaver is presented. The band-shaped muscle was located at the ulnar side of the hand between the fourth and fifth extensors. It originated from the deep carpal fascia and inserted to the extensor tendons of the fourth and fifth fingers with a tendon and a slip, respectively. The origin, insertion, and location of the muscle differ from those previously reported: with these anatomic features, the muscle variation cannot be placed into the current classifications. The phylogenetic and ontogenetic implications of the muscle are reviewed. Copyright (C) 1998 by the American Society for Surgery of the Hand.